PENGARUH TANIN-FORMALDEHIDA TERHADAP SIFAT FISIK DAN KETAHANAN TARIK PAPAN SERAT YANG DIBUAT DENGAN PROSES BASAH - Bambang Wiyono (Jurnal Penelitian Hasil Hutan, 1988)
Condensed-tannin from bark of  Pinus merkusii  Jungh  et de  Vriese,  can react  with  formaldehyde in alkali or acid condition  to form  tannin-formaldehyde. The  reaction  product is assumed  to be an excellent  sizing  material for fiberboard manufactures. The  purpose   of  this  research  is  to  study   the  effect   of  tannin-formaldehyde  sizing  on  moisture  content, density,     thickness, water absorption, thickness swelling, and tensile strength parallel to surface of  fiber board properties. The amount  of  tannin-formaldehyde added  to pulp  consisting  of 0,3,6, 9 and  1.2 percent based on  oven dry  pulp.    Results indicate  that  the  addition of  tannin-formaldehyde during  the  fiberboard  making  process  has a highly significant  effect on  reducing water absorption and  thickness swelling.   Similarly, the tensile strength  parallel to surface  of fiberboard was  significantly  improved by  adding  tannin-formaldehyde.  Overall  improvement  of  fiberboard  properties  could  be achieved  by adding 12 percent of  the sizing  agent to the  stock.